2019
DOI: 10.1101/838748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antithetic integral feedback for the robust control of monostable and oscillatory biomolecular circuits

Abstract: Biomolecular feedback systems are now a central application area of interest within control theory. While classical control techniques provide invaluable insight into the function and design of both natural and synthetic biomolecular systems, there are certain aspects of biological control that have proven difficult to analyze with traditional methods. To this end, we describe here how the recently developed tools of dominance analysis can be used to gain insight into the nonlinear behavior of the antithetic i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…and our assumptions on the sign pattern of the Jacobian imply that (J(x(t))) [2] is Metzler for all t ≥ 0. Thus (19) implies that (Φ(t)) (2) ≥ 0 for all t ≥ 0.…”
Section: Proof Of Main Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…and our assumptions on the sign pattern of the Jacobian imply that (J(x(t))) [2] is Metzler for all t ≥ 0. Thus (19) implies that (Φ(t)) (2) ≥ 0 for all t ≥ 0.…”
Section: Proof Of Main Resultsmentioning
confidence: 99%
“…Remark 3. Our goal in computing J [2] was to prove that (19) is a cooperative dynamical system. We note in passing that under certain conditions J [2] can also be used to rule out the existence of limit cycles [18].…”
Section: Proof Of Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [38,39], the authors determined analytic conditions on the reaction rate parameters of the antithetic feedback network such that the linearized closed loop system is stable. Subsequent research also discussed the stability of the nonlinear dynamics of closed loop antithetic feedback network [44,45]. Without stability, the antithetic feedback control would not be able to track the reference signal; instead, it would oscillate indefinitely.…”
Section: A Mathematical Model Of Antithetic Feedback Network With Con...mentioning
confidence: 99%
“…Indeed, in the previous synthetic biological implementations of antithetic feedback in E. coli and S. cerevisiae, the antithetic feedback controller's relative steady-state error (as normalized to the reference) has been measured to be 5-50% [28,31]. Another consideration is the stability of the closed-loop antithetic feedback system since theoretical studies have demonstrated that, depending on the reaction rate parameters, the antithetic controller can become unstable and periodic oscillations can arise [39,42,44,45]. Therefore, it is important to consider how the stability, robustness, and steady-state error (performance) of the antithetic feedback motif depend on its synthetic biological implementation and to study in depth how to tune these properties [28,46].…”
Section: Introductionmentioning
confidence: 99%